Picture a man...Busa Award Lecture, Debrecen, Hungary, 6 July 1998. - Busa, R (Literary & Linguistic Computing, 1999)
The article presents a speech by Roberto Busa, first recipient of the Roberto Busa Award, delivered at a lecture during the award presentation held in Debrecen, Hungary on July 6, 1998, in which he discussed data bank and informatics publishing, the use of native language, and the need to re-establish, re-format, and re-formulate traditional morphology, lexicon, and syntax.